Addressing the Digital Divide: A Study on the Predictors of Government E-Service Utilization in Thailand - Natnaree Wongmith; Ornvipa Phuengngern (International Telecommunications Society (ITS), 2024)
With the advancement of digital technology, governments have created more channels for citizens to access accessing government services. However, there are disparities in accessibility and utilization of the services, leading to uneven benefits across the population. This study investigated the determinant factors of e-government service utilization and identified the sociodemographic characteristics and technological usage of individuals who used and did not use the services. The study analyzed data from 2023 Nationwide Telecommunications Usage Behavior and Device Access Survey (n = 42,335). Chi-squared test, z-test and, and binary logistic regression were employed to analyze the data. The findings indicated that age, education, geographical location, mobile broadband technology, and type of data cap are significant predictors of e-government utilization.
Keywords: 330; Digital divide; E-Government service utilization; Mobile internet access; Prepaid service; Postpaid service; Survey research